Thermodynamics of the structural transition in metal–organic frameworks. Issue 10 (17th November 2015) - Rodriguez, J.; Beurroies, I.; Coulet, M.-V.; Fabry, P.; Devic, T.; Serre, C.; Denoyel, R.; Llewellyn, P. L.
Abstract : A thermodynamic study of the structural large-pore (LP) to narrow pore (NP) transition in various Metal Organic Frameworks (MOFs) is presented. Abstract : A thermodynamic study of the structural large-pore (LP) to narrow pore (NP) transition in various Metal Organic Frameworks (MOFs) is presented. First, the pressure induced transition at a constant temperature is investigated using a Tian-Calvet microcalorimeter set-up equipped with a high pressure cell. This device permits simultaneous measurements of the mechanical work and heat associated with the LP → NP transition. It is shown that MIL-53(Al) and MIL-53(Cr) have similar thermodynamic and mechanical behaviour whilst the MIL-47(V) system is characterized by much higher transition energy and mechanical work. Second, the temperature induced transition at ambient pressure is studied by means of differential scanning calorimetry (DSC) combined with X-ray absorption spectroscopy. This set-up enables one to follow simultaneously the structural changes associated with the phase transition detected by DSC. The MIL-53(Cr)-Br functionalized MOF is chosen here as a case study where both energetics and structural changes are discussed.